Сленг як особливість ідіостилю Кузьми Скрябіна (Андрія Кузьменка) - Гаврилюк, Наталія; Зозюк, Ірина; Gavryljuk, Natalija; Zozjuk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано особливості сленговживання в художніх текстах Кузьми Скрябіна, виявлено основні функції сленгізмів у творах письменника, описано тематичні групи сленгізмів як специфічних репрезентантів ключових цінностей та особливостей буття сучасного соціуму, охарактеризовано сленгові одиниці за походженням. In the article the features of the use of slang in artistic texts of Kuz'ma Skryabin are analysed, the basic functions of slangism in works of writer are exposed, the thematic groups of slangism as specific reprezentantov of key values and features of life of modern society are described, slang units are described originally. Kuz'ma Skryabin uses a slang mainly for Лінгвостилістика ХХІ століття: стан і перспективи 45 expression irony, emotional-expressive description, realistic image of features of residence and speech of the represented personages. In works of writer a far is present slangisms, designating an alcohol, drugs, money, and also nominations of person, a positive or negative estimation is stopped up in which. Young people always sharply react on the topical problems of society. Majority of slangism is had the Russian, English, and also Ukrainian origin, that testifies to development of the Ukrainian slang.
Slang as a feature of individual style of Kuz'ma Skryabin (Andriy Kuz'menko)
Keywords: сленг; сленгізм; соціолект; тематична група; індивідуальний стиль; slang; slangism; sociolect; thematic group; individual style